2018
DOI: 10.4236/ce.2018.914172
|View full text |Cite
|
Sign up to set email alerts
|

Instructional Model for Social Skills Intervention Children with Visual Impairment

Abstract: This paper discusses a proposed instruction model for intervention of social skills children with visual impairment. Intervention model based on Badura's Social Cognitive Learning Theory were proposed to help students with visual impairment in the development of their social skills. The emphasis of the theory was based on imitation, environment and cognition. The three elements are interrelated in the development of social skills and individual behavior. The theory stressed the process of learning behavior thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Parents involved in assisting their children to complete their homework can upgrade students' achievement levels (Aida & Zolkepli, 2014;Manisah, Azleen, Norshidah & Majid, 2017). The continuity of learning in school and at home, not only helps in academic attainment but also helps remedy problematic behavior among students (Norshidah & Khalim, 2018). Research findings also illustrate that time constraint is the main obstacle faced by parents in involving themselves in discipline management of their special children.…”
Section: Discussionmentioning
confidence: 82%
“…Parents involved in assisting their children to complete their homework can upgrade students' achievement levels (Aida & Zolkepli, 2014;Manisah, Azleen, Norshidah & Majid, 2017). The continuity of learning in school and at home, not only helps in academic attainment but also helps remedy problematic behavior among students (Norshidah & Khalim, 2018). Research findings also illustrate that time constraint is the main obstacle faced by parents in involving themselves in discipline management of their special children.…”
Section: Discussionmentioning
confidence: 82%
“…Parental encouragement, prizes, and punishments are common ways to motivate children. By using this strategy, young people may develop into responsible adults (Salleh & Zainal, 2018). The development of children's physical and mental health as well as a growth in their engagement in sports activities were examined in a research study.…”
Section: Discussionmentioning
confidence: 99%
“…Parents are likely to offer motivation by encouraging, offering rewards and giving penalties. By this method, kids may grow up to be living like responsible people (Salleh & Zainal, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have proposed various guidelines to enhance the educational environment in an inclusive setting. Studies have implied that disability contributes to the poor personal development of social skills; thus, there is a need for intervention to augment the acquisition of the required skills for social interaction and enable effective socialization with their sighted peers [8][9][10]. Recent studies have shown that it is necessary for students with visual impairment within inclusive settings to receive special education services so that they can participate in class activities [11,12].…”
Section: Introductionmentioning
confidence: 99%